Sustainability and urban innovation: Obstacles and perspectives in the energy transition in smart cities (Research, Society and Development, 2025)
The objective of this article is to understand the main challenges and opportunities that permeate the energy transition in smart cities, with a focus on Brazilian experiences of urban sandboxes. The methodology adopts a qualitative approach, with a literature review on urban innovation, energy transition, smart cities and urban sandboxes, in addition to the analysis of public policy documents and innovation programs in Brazil and in other countries, with an emphasis on the impacts of urban sandboxes and on how these experiences have driven innovation in sectors such as electric mobility, smart public lighting and energy monitoring. It is concluded that experimental environments, such as urban sandboxes, can be a strategic tool to accelerate the energy transition in cities; integrating innovative energy technologies within flexible regulatory contexts enables agile responses to urban challenges and promotes a more resilient and sustainable future.